The philosophy of Swāmī Rāma Tīrtha - Maheshwari, Hazarilal 1921-2002 (New Delhi Readworthy, 2009)
Swami Rama Tirtha, 1873-1906, Hindu religious leader
Includes index. - Includes bibliographical references (p. [227]-232)
Archivierung prüfen
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Rama Tirtha 1873-1906; Vedanta; Philosophy, Hindu